Bambatha after Mome: Dead or Alive? (Historia, 2021)
EnglishBambatha kaMancinza, chief of the Amazondi in the Greytown district, was an important leader and probably the best known personality in the rebellion against the poll tax imposed by the Natal colonial government in 1906. Colonial authorities stated that he was killed in battle at the Mome Gorge on 10 June 1906, and cited witnesses who recognized his body and head (decapitated for proof and then buried with the body). This served their immediate purpose of dispiriting the rebels and bringing the rebellion in Zululand to a speedy close. The evidence was persuasive, but not conclusive. Other reports circulated that Bambatha had escaped from the battlefield. These fed into popular rumours that he was preparing somehow to renew the rebellion in connexion with Dinuzulu, who was generally regarded as the successor to the Zulu throne, although not officially recognized as such. These rumours flourished and spawned various reports of his activities and whereabouts during the unsettled times just after the rebellion. Even the colonial authorities halfbelieved them. Dinuzulu's arrest and trial in 1908-1909 abruptly deflated them. Dinuzulu was essential to a renewal of the rebellion, Bambatha was not. Examination of the reports and rumours also show that there was no substantial evidence from anyone who could positively identify and had actually seen Bambatha after Mome. It seems most probable therefore that he had died there, although perhaps not in the manner the colonial authorities described. None the less, a local legend has persisted, especially among Zondi people, that he escaped to live and die either in Zululand or in Mozambique.   AfrikaansBambatha na Mome: Dood of Lewendig? Bambatha (Bhambatha, Bambada, Bhambada)Bambatha kaMancinza, hoof van die Amazondi in die Greytown Distrik, was ’n belangrike leier en waarskynlik die prominentste persoonlikheid in die rebellie teen die hoofbelasting wat in 1906 deur die Natalse koloniale regering ingestel is. Koloniale owerhede het verklaar dat hy op 10 Junie 1906 in die Slag van Mome Kloof gedood is en dat getuies sy liggaam en hoof geëien het. Hy is onthoof vir uitkenningsdoeleindes – sy kop is daarna saam met sy liggaam begrawe. Dit het die owerhede se onmiddellike doel gedien, naamlik om die rebelle te ontmoedig en die opstand in Zululand tot ’n spoedige einde te bring. Die bewyse was oortuigend, maar nie beslissend nie. Ander berigte het die rondte gedoen dat Bambatha van die oorlogsveld ontsnap het. Dit het populêre gerugte versterk dat hy, in samewerking met Dinuzulu, besig was om op een of ander wyse ’n herlewing van die rebellie te beplan. Dinuzulu is algemeen as die Zulu-troonopvolger beskou, hoewel hy nie amptelik as sodanig gereken is nie. Hierdie gerugte het gefloreer en aanleiding gegee tot verskeie berigte oor Bambatha se aktiwiteite en posisie tydens die ontwrigting pas na die rebellie. Selfs die koloniale owerhede het dit deels geglo. Dinuzulu se arrestasie en verhoor in 1908-1909 het die gerugte plotseling ongedaan gemaak. Dinuzulu was essensieel tot die herlewing van die rebellie, maar Bambatha was nie. ’n Ondersoek na die verslae en gerugte dui ook daarop dat daar geen substansiële bewys was dat daar enigeen was wat Bambatha na Mome positief kon identifiseer of inderdaad gesien het nie. Dit lyk dus die waarskynlikste dat hy wel daar gesterf het, hoewel miskien nie op die presiese manier waarop die koloniale owerhede beskryf het nie. Nietemin het ’n legende dat hy ontsnap het om óf in Zululand, óf Mosambiek te gaan woon en sterf, veral onder die Zondimense bly voortleef.
Keywords: Bambatha (Bhambatha, Bambada, Bhambada); Zulu rebellion of 1906; Dinuzulu (Dinizulu); Mome (Mhome); Natal; Zulu-rebellie van 1906